Distribution pattern and identity of powdery mildew of composites in the districts of Agra division - MOHD. AKRAM, S. IQBAL HUSAIN and (Indian Phytopathology, 2002)
The distribution pattern and identity of powdery mildew species associated with ornamental crops in the districts of Agra division in Uttar Pradesh, India, were investigated during disease surveys conducted in 1993 and 1994. Powdery mildew was widespread appearing on both cultivated and wild composites in almost every locality in the study area. Calendula officinalis was the most severely affected crop. Dimorphotheca sinuata and Zinnia elegans were disease-free in most of the localities surveyed except Aligarh and Mathura districts. Due to the absence of teleomorphs, the causal agents of the disease, Erysiphe cichoracearum and Sphaerotheca fuliginea, were identified using anamorphic characters. E. cichoracearum was widespread causing disease on Chrysanthemum coronarium, Cosmos sulphureus, Dahlia variabilis, Helianthus annuus, Xanthium strumarium and Zinnia elegans, whereas S. fuliginea was confined to Calendula officinalis, Dimorphotheca sinuata and Eclipta alba. The severity of powdery mildew onthe different composite species in all the localities surveyed is presented.